Establishment of a Limited Liability Company in Indonesia - Ibrahim Nainggolan (International Journal Reglement & Society (IJRS), 2022)
The business world is currently experiencing very rapid development. In carrying out their business, many entrepreneurs choose the form of a Limited Liability Company, among others because: Capital/shares, have assets that are separate from the assets of the shareholders, shareholders have limited liability, there is a separation of functions between shareholders and management or directors, has commissioners. which functions as a supervisor, and the highest power is at the General Meeting of Shareholders (GMS). A limited liability company is a legal entity which is a capital partnership, established based on an agreement, conducting business activities with the authorized capital which is entirely divided into shares, and fulfilling the requirements applied in the law. Regulations in the field of Limited Liability Companies have undergone several changes. Currently, it is regulated in Law Number 40 of 2007 concerning Limited Liability Companies, replacing the previous law, with the aim of being more in line with current legal developments and able to accommodate the needs of the community